Contrast-enhanced ultrasound diagnosis and efficacy prediction of primary breast lymphoma: a case report and literature review - Tang, Siqi; Ma, Yuqin; Zhan, Xiaochen; Lu, Jianghao; Wu, Tingting; Zhou, Peng (Frontiers in Oncology, 2025)
Primary breast lymphoma (PBL) is a rare entity, accounting for less than 1% of all breast malignancies. PBL is often difficult to differentiate from other benign and malignant breast tumors. This case report describes the contrast-enhanced ultrasound (CEUS) diagnosis of PBL in a 34-year-old female patient, initially presenting with a left breast lump. CEUS revealed some distinctive features: diffuse hyperenhancement with the “floating vessel” sign. These findings enabled a timely diagnosis. Histopathological analysis confirmed diffuse large B-cell lymphoma. After more than two years of chemotherapy, CEUS revealed significant lesion shrinkage with well-defined margins alongside delayed arrival time, reduced peak intensity, and a decreased area under the curve, collectively indicating a favorable chemotherapeutic response. Eventually, the patient underwent surgery, and pathological examination confirmed the absence of significant lymphoma cells following chemotherapy. This case underscores the value of CEUS in identifying PBL and assessing chemotherapy efficacy through qualitative characterization and quantitative parameters, thereby demonstrating its dual role in both lesion identification and therapeutic monitoring. It also emphasizes the significance of including lymphoma in the differential diagnosis of breast masses.